2013
DOI: 10.1111/imm.12108
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD8+ T cells in triggering reversal reaction in HIV/leprosy patients

Abstract: Summary It has been reported that the initiation of highly active anti‐retroviral therapy (HAART) is associated with the development of reversal reaction (RR) in co‐infected HIV/leprosy patients. Nevertheless, the impact of HIV and HAART on the cellular immune response to Mycobacterium leprae (ML) remains unknown. In the present study, we observed that ex vivo peripheral blood mononuclear cells (PBMCs) of both RR and RR/HIV patients presented increased percentages of activated CD4+ T cells when compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Similar findings were disclosed by Oliveira et al ., who also demonstrated an increase in both CD4+ and CD8+ TEMRA cells in peripheral blood leucocytes in co-infected HIV/leprosy patients showing T1R. Authors also suggested that CD8+ T EM cells triggered T1R in HIV/leprosy patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were disclosed by Oliveira et al ., who also demonstrated an increase in both CD4+ and CD8+ TEMRA cells in peripheral blood leucocytes in co-infected HIV/leprosy patients showing T1R. Authors also suggested that CD8+ T EM cells triggered T1R in HIV/leprosy patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…T CD8+ lymphocytes are primarily involved in the development of cytotoxicity ( 50 , 51 ). Studies have shown that T CD8+ cells participate in mechanisms that lead to the destruction of the bacillus in coinfection with HIV in a reverse reaction ( 52 , 53 ). In this context, by recognizing virus-infected cells, T CD8+ cells would promote the release of granzymes and perforins that destroy the coinfected cells in patients with a type-1 reverse reaction ( 52 , 53 ).…”
Section: Immune Response In Leprosymentioning
confidence: 99%
“…Studies have shown that T CD8+ cells participate in mechanisms that lead to the destruction of the bacillus in coinfection with HIV in a reverse reaction ( 52 , 53 ). In this context, by recognizing virus-infected cells, T CD8+ cells would promote the release of granzymes and perforins that destroy the coinfected cells in patients with a type-1 reverse reaction ( 52 , 53 ). The response of B lymphocytes is primarily associated with the humoral response, and some studies on leprosy have demonstrated increased expression of CD20 in the tuberculoid form and borderline tuberculoid form in a reverse reaction ( 40 , 54 ).…”
Section: Immune Response In Leprosymentioning
confidence: 99%
“…Similar to our findings, Oliveira et al also demonstrated an increase in CD8+ T CM cells in co-infected HIV/leprosy patients showing an acute inflammatory manifestation referred to as reversal reaction. The authors also suggested that CD8+ T CM cells may contribute to these episodes [ 27 ]. Interestingly, the negative CD86 expression on both APC did not prevent the significant increase in both CD4+ and CD8+ T CM cells in our patients in response to the ML antigen.…”
Section: Discussionmentioning
confidence: 99%